2009
DOI: 10.1080/00103620902896712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Ignition Method and the Perchloric Acid Digestion Method for the Determination of Total Phosphorus in Agricultural Soils of Taiwan

Abstract: The ignition method and the perchloric acid (HClO 4 ) digestion method for the determination of total phosphorus (P) content in 65 agricultural soils of Taiwan were compared. The average amount of total P obtained by the ignition method was 4.3% less than that obtained by the HClO 4 method. There was a wide range of variation, from 37% less to 21% more in the ignition method than those results obtained by the HClO 4 digestion method. Because the ignition method can also be used for the estimation of soil organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…In most cases, the Pt-H2SO4 values are lower; in CPT-9, the value was slightly higher than the Pt-HClO4 value. These data are comparable with data reported in the literature [3,42]. Other authors have found that dry combustion followed by P extraction in 0.5 M H2SO4 slightly underestimated Pt, which was attributed to incomplete oxidation of organic matter, volatilization of P, and formation of insoluble P crystals during dry combustion at 550 °C [64,65].…”
Section: Dynamics Of P Forms In Compost At Different Maturity Stagessupporting
confidence: 90%
See 1 more Smart Citation
“…In most cases, the Pt-H2SO4 values are lower; in CPT-9, the value was slightly higher than the Pt-HClO4 value. These data are comparable with data reported in the literature [3,42]. Other authors have found that dry combustion followed by P extraction in 0.5 M H2SO4 slightly underestimated Pt, which was attributed to incomplete oxidation of organic matter, volatilization of P, and formation of insoluble P crystals during dry combustion at 550 °C [64,65].…”
Section: Dynamics Of P Forms In Compost At Different Maturity Stagessupporting
confidence: 90%
“…The following phosphorus forms were determined in the research material: the total content of P after digestion in concentrated HClO 4 [41,42] in the aluminium block at a temperature of 130 • C (P t ); the content of organic P (P org ), calculated from the differences between the P content measured in 0.5 M H 2 SO 4 extracts of the samples burned in a furnace at 550 • C for 2 h (P t ) and samples not subjected to burning (P min ) [43]; the P oxalic-oxalate extractable (P ox ), according to Tamm method, using a mixture of 0.175…”
Section: Phosphorus Extraction Proceduresmentioning
confidence: 99%
“…Soil and water were mixed at a mass ratio of 1:1, and soil conductivity was determined after shaking for 1 h [40]. Soil total organic carbon content was determined via the potassium dichromate oxidation method [41], soil nitrate nitrogen content was determined via UV absorption spectrometry [42], soil total phosphorus content was determined via the perchloric acid ablation method [42], and soil total potassium content was determined via flame photometry [43]. The available phosphorus was determined via the sodium bicarbonate method, and the available potassium was determined using atomic absorption spectrophotometry [44,45].…”
Section: Soil Analysismentioning
confidence: 99%